2008
DOI: 10.1111/j.1744-7909.2007.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide in Plants: a Versatile Molecule of the Reactive Oxygen Species Network

Abstract: Plants often face the challenge of severe environmental conditions, which include various biotic and abiotic stresses that exert adverse effects on plant growth and development. During evolution, plants have evolved complex regulatory mechanisms to adapt to various environmental stressors. One of the consequences of stress is an increase in the cellular concentration of reactive oxygen species (ROS), which are subsequently converted to hydrogen peroxide (H(2)O(2)). Even under normal conditions, higher plants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
359
1
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(381 citation statements)
references
References 121 publications
(154 reference statements)
9
359
1
12
Order By: Relevance
“…Under high concentrations of H 2 O 2 , photo-damage rather than photo-inhibition occurred, which was indicated by the irreversible F v /F m changes, even after dark adaptation for a long time (Bjorkman et al, 1988;Critchley and Russell, 1994;Guo et al, 1996). In all the above-mentioned experiments, low concentrations (10 mg/L) of H 2 O 2 caused F v /F m to rise slightly rather than decrease, which might be attributed to activation of some related enzyme systems (Desikan et al, 2001;Neill et al, 2002;Cheng and Song, 2006;Quan et al, 2008). However, a concentration as low as 60 mg/L could completely inhibit the photosynthetic activity of algae in 2 h, which indicated that H 2 O 2 was an effective algaecide and a good candidate for emergent removal of cyanobacterial blooms.…”
Section: Discussionmentioning
confidence: 93%
“…Under high concentrations of H 2 O 2 , photo-damage rather than photo-inhibition occurred, which was indicated by the irreversible F v /F m changes, even after dark adaptation for a long time (Bjorkman et al, 1988;Critchley and Russell, 1994;Guo et al, 1996). In all the above-mentioned experiments, low concentrations (10 mg/L) of H 2 O 2 caused F v /F m to rise slightly rather than decrease, which might be attributed to activation of some related enzyme systems (Desikan et al, 2001;Neill et al, 2002;Cheng and Song, 2006;Quan et al, 2008). However, a concentration as low as 60 mg/L could completely inhibit the photosynthetic activity of algae in 2 h, which indicated that H 2 O 2 was an effective algaecide and a good candidate for emergent removal of cyanobacterial blooms.…”
Section: Discussionmentioning
confidence: 93%
“…H 2 O 2 is beginning to be accepted as a secondary messenger for signals generated by the ROS due to its considerably long half-life and high permeability through the membranes (Quan et al, 2008). However, the biological effects of H 2 O 2 have shown to be dependent not only on the concentration, but also on the production site, on the development stage of the plant and on the previous exposure of the plant to other types of stress (Petrov & van Breusegem, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidative property of GSH is involved in the reduction of H 2 O 2 , which in turn alters the redox state of the GSH/GSSG couple. The GSH/GSSG ratio and H 2 O 2 perform a signaling role by affecting proteins during transcription, translation, post-translational processes, and the metabolic processes conducted by the proteins (Dietz 2008;Quan et al 2008). H 2 O 2 regulates the GSH pool in maize under various abiotic stresses and imposes posttranslational regulation of c-ECS and GR transcript levels, thereby controlling GSH synthesis, the GSH/GSSG ratio, and GR activity (Kell} os et al 2008).…”
Section: Signaling Cross Talk Of Glutathionementioning
confidence: 99%